Peranan Keterampilan Pegawai Dalam Pengelolaan Surat Menyurat Terhadap Efektivitas Kinerja Pegawai Di Dinas Perindustrian Perdagangan Energi Dan Sumber Daya Mineral Provinsi Sumatera Utara - Diah Rizki Syahrani Nst; Arnida Wahyuni Lubis (Jurnal Akuntan Publik, 2023)
The background to this research is that companies consist of a number of individuals who work together to achieve various goals in the fields of business, profession, social, and so on. One important thing is to provide the best service to external parties by carrying out written communication between agencies related to the company. The importance of the employee's role in managing employee activities cannot be ignored. This can be done in large or small scale companies, or even in the company's activities themselves. Communication between employees, involving planning, organizing, determining, distributing and delivering activities, is a very important factor for the success of a company, one of which is in terms of correspondence. The aim of this research is to understand, identify and analyze the effectiveness of employee performance in managing correspondence at the Department of Industry, Trade, Energy and Mineral Resources of North Sumatra Province. The results can be concluded that the effectiveness of employee performance in the role of employee skills in managing correspondence in the Department of Industry, Trade, Energy and Mineral Resources of North Sumatra Province has indicators in assessing it, including work performance results, discipline, coordination, skills, responsibility, Employee understanding of the tasks/fields to be carried out, Receive complaints from superiors regarding the results of the work carried out.